2010
DOI: 10.1002/adma.200901383
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene Sensitized Silicon for Near‐ to Mid‐Infrared Light Detection

Abstract: Detection of light in the near-to mid-infrared (IR) spectral range is a technology in demand for many applications such as optical data transmission (1.55 mm), contrast enhancement for imaging systems in foggy environments, and quality control. Most of the optoelectronic devices on the market are based on the rather expensive III-V compound technology and, as a result, the monolithic integration into the well-established and cheap silicon-based complementary metal oxide semiconductor (CMOS) production process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
2
19
2
Order By: Relevance
“…The results for the energy level structure across the p-Si/PCBM interface obtained here by electrical methods are in full agreement with the onset energy of the photocurrent as reported in Ref. 2, confirming the previously presented model for photocurrent generation at the interface due to an enhancement of the hole capture rate of the PCBM LUMO level by photon absorption.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…The results for the energy level structure across the p-Si/PCBM interface obtained here by electrical methods are in full agreement with the onset energy of the photocurrent as reported in Ref. 2, confirming the previously presented model for photocurrent generation at the interface due to an enhancement of the hole capture rate of the PCBM LUMO level by photon absorption.…”
Section: Resultssupporting
confidence: 79%
“…The energy difference between VB of p-Si and LUMO of PCBM is identified as interface barrier height and defines the onset of the spectrally resolved photocurrent reported previously. 2 Based on the detailed understanding of the diode operation principle, further improvements of the device with respect to its application as infrared photodetector compatible with standard Si technology 21 as well as the development of photodetectors based on alternative organic semiconductors becomes possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interest in organic/inorganic heterojunction devices began in the 1980s, and since then several models have been developed to understand the electrical characteristics of such junctions. [9][10][11] In 2010, it was reported that a heterojunction of a solution-processed fullerene (C 60 ) derivative and p-Si displayed a photovoltaic effect down to photon energies of around 0.55 eV (2.25 lm), 12 with mediocre NIR responsivity a)…”
mentioning
confidence: 99%